N6-Methyladenosine Modification Opens a New Chapter in Circular RNA Biology - Wu, Jun; Guo, Xin; Wen, Yi; Huang, Shangqing; Yuan, Xiaohui; Tang, Lijun; Sun, Hongyu (Frontiers in Cell and Developmental Biology, 2021)
As the most abundant internal modification in eukaryotic cells, N6-methyladenosine (m6A) in mRNA has shown widespread regulatory roles in a variety of physiological processes and disease progressions. Circular RNAs (circRNAs) are a class of covalently closed circular RNA molecules and play an essential role in the pathogenesis of various diseases. Recently, accumulating evidence has shown that m6A modification is widely existed in circRNAs and found its key biological functions in regulating circRNA metabolism, including biogenesis, translation, degradation and cellular localization. Through regulating circRNAs, studies have shown the important roles of m6A modification in circRNAs during immunity and multiple diseases, which represents a new layer of control in physiological processes and disease progressions. In this review, we focused on the roles played by m6A in circRNA metabolism, summarized the regulatory mechanisms of m6A-modified circRNAs in immunity and diseases, and discussed the current challenges to study m6A modification in circRNAs and the possible future directions, providing a comprehensive insight into understanding m6A modification of circRNAs in RNA epigenetics.